Minimizing Rental Costs in Flowshop Scheduling with the NEH (Nawaz, Enscor, and Ham) Method - Muhammad Faudzi; M Adib Jauhari Dwi Putra (Urecol Journal. Part D: Applied Sciences, 2021)
This study discusses how to minimize rental costs in flowshop scheduling. Optimal scheduling time was obtained using the Nawaz, Enscor, and Ham (NEH) method. The right time to rent a machine is obtained by comparing the utility of the machine with the processing time of each machine with the processing time of each job on the machine. We apply this research in CV. SAMHARI which is a company that manufactures sandals. After applying the rental cost minimization method at the research site, we found that CV. SAMHARI can minimize the rental costs incurred by Rp. 273700.